PEREMPUAN PEGAWAI NEGERI SIPIL DALAM PERNIKAHAN POLIGINI (Studi Fenomenologi Mengenai Perempuan PNS yang Terikat dalam Pernikahan Poligini di Kabupaten Karawang) - Nursanti, Siti (Majalah Ilmiah SOLUSI, 2015)
The study is titled "Women In Marriage Polygyny " This stems from the rise of polygynous marriages occur among the people of Indonesia , especially among civil servants in Karawang district . Polygynous marriage is a form of marriage that is undertaken by one man with several women in the same time period. Polygynous marriage is a marriage that has not been widely accepted in society. Polygynous marriage may be performed in the Islamic religion with the terms and conditions applicable. For PNS Women polygynous marriages may be performed with the terms must obtain permission from the first wife. This study wants to examine the significance of women, marriage and the meaning of women's experience of civil servants communication in polygynous marriages in karawang district. The theory is used to form the framework is Symbolic Interaction theory of George Herbert Mead and Alferd Schutz Theory Phenomenology. Researchers using qualitative methods through a phenomenologic approach to tradition. This tradition seeks to uncover and understand the reality of the research is based on the perspective of the research subjects. In this study using eight informants as sources of information. The results showed that PNS Women in polygynous marriages bekeja interpret that women as a form of self-actualization, recognition in the community and economic independence. Polygynous marriage is a test of patience, protection and berpasangan needs. Communication experiences of women civil servants in polygynous marriages as a form of torture against himself and his family, the shape and strength of true happiness and a test of patience in undergoing a test of life. Keywords: WomenMarriagePolygyny, Symbolic Interaction, Phenomenology